Pembelajaran Berdiferensiasi Menulis Teks Eksposisi Pada Peserta Didik Kesetaraan - Qholisna Munanar (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This study highlights the importance of differentiated learning in the educational context, particularly for equivalency program students. Education serves as a process for delivering culture that supports the development of attitudes and knowledge. Within the framework of the Merdeka Curriculum, teachers are expected to innovate in delivering material and instilling character values. The goal of differentiated learning is to meet the diverse needs of students, considering the unique characteristics of each individual that influence their learning styles. There are four main components of differentiated learning: differentiation of content, process, product, and learning environment. This research employs a qualitative approach using a case study method to explore the implementation of differentiated learning in writing expository texts. The findings indicate that despite challenges such as a lack of training for teachers, the application of appropriate strategies can enhance students' writing skills. This study recommends further support for teachers to effectively implement differentiated learning, creating meaningful and inclusive learning experiences for students.